Customer Relationship Management and Service Quality in Assessing Customer Loyalty - Setiyani Hidayati; Khusnik Hudzafidah; Renny Augustina; Trivosa Aprilia Novadiani Haidiputri (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: The purpose of this study is to analyze and increase customer loyalty through customer relationship management and good service quality. Design/methodology/approach: This study uses a quantitative descriptive method, with a sampling technique in the form of purposive sampling. Analysis using multiple linear regression. Findings: The results showed that customer relationship management is able to provide an important role in increasing customer loyalty. Providing good service quality is also able to increase customer loyalty. Research limitations/implications: This research has implications for the problems that exist in UD. Batik Manggur Probolinggo in overcoming customer loyalty problems. Practical implications: For investors or interested parties in overcoming customer loyalty, customer relationship management practices and service quality need to be maintained properly. Originality/value: This paper is original Paper type: Research paper